Laparoscopic Cholecystectomy: An Initial Clinical Experience at Faridpur District (Journal of Current and Advance Medical Research, 2015)
Background: Laparoscopic cholecystectomy quickly emerged as an alternative to open cholecystectomy. However its safety, efficacy, and morbidity have yet to be fully evaluated.Objective: The purpose of the present study was to determine the efficacy and safety of laparoscopic cholecystectomy Procedure in the removal of gall bladder stones at Faridpur district-one of the remote district of Bangladesh.Methodology: A prospective, nonrandomized, open label Consecutive study was carried out at Faridpur district using laparoscopic cholecystectomy (LC) procedure for the symptomatic treatment of Gall bladder stones. For this purpose a total number of 145 patients having conclusively diagnosed as gall bladder stones were enrolled. LC procedure was performed by North American technique-a well established and standard procedure described earlier for the purpose. The key variables studied were average operating room time, condition of the gall bladder, the presence or absence of stones, the character of stones, post-operative complicates and duration of hospital stay.Result: The study revealed that among 145 patients 83.4% were female with an average age of 40.3 years. The average operating time required was 130 minutes. Gall bladder was thickened but was free from adhesion in 96.5% cases and stones' only 3.45% patients needed open method due to fibrosis and adhesion of the gall bladder with omentum and gut. The duration of hospital or clinic stay following LC was 3.5 days. Evidence of infection like fever, pain etc. was seen only in 2.75% cases. Bleeding was present in 2.06% cases. This was corrected after blood transfusion. No injury to the common bile duct or any of the bile duct or any of the blood vessels was observed. Similarly no evidence of malignancy was seen in any of the gall bladder removed.Conclusion: The present study concludes that laparoscopic cholecystectomy is a safe, minimal invasive, cost-effective and safe procedure for the symptomatic treatment of gall bladder stones.Journal of Current and Advance Medical Research, 2015;2(2):30-33